2022
DOI: 10.1186/s40348-022-00142-2
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs as regulators of pediatric acute myeloid leukemia

Abstract: Long noncoding RNAs (lncRNAs) are increasingly emerging as regulators across human development and disease, and many have been described in the context of hematopoiesis and leukemogenesis. These studies have yielded new molecular insights into the contribution of lncRNAs to AML development and revealed connections between lncRNA expression and clinical parameters in AML patients. In this mini review, we illustrate the versatile functions of lncRNAs in AML, with a focus on pediatric AML, and present examples th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…In a more clinically relevant scenario, UCA1 knockdown was shown to suppress the chemoresistance of pediatric AML by inhibiting glycolysis through direct binding with miR-125a (Zhang Y. et al, 2018). There are several examples of lncRNAs that have been characterized in pediatric AML that show correlations to patient prognosis and survival; such examples were summarized in a recent review by Neyazi et al (2022). In a recent comprehensive study, Vanhooren et al (2022) performed a miRNA-lncRNA network analysis in leukemic stem cells (LSCs) and leukemic blasts (L-blasts) from pediatric AML patients; this study identified several novel lncRNAs and miRNAs in pediatric AML that could become new biomarkers for risk stratification and targeted therapy in the future.…”
Section: Lncrnas In Pediatric Amlmentioning
confidence: 99%
“…In a more clinically relevant scenario, UCA1 knockdown was shown to suppress the chemoresistance of pediatric AML by inhibiting glycolysis through direct binding with miR-125a (Zhang Y. et al, 2018). There are several examples of lncRNAs that have been characterized in pediatric AML that show correlations to patient prognosis and survival; such examples were summarized in a recent review by Neyazi et al (2022). In a recent comprehensive study, Vanhooren et al (2022) performed a miRNA-lncRNA network analysis in leukemic stem cells (LSCs) and leukemic blasts (L-blasts) from pediatric AML patients; this study identified several novel lncRNAs and miRNAs in pediatric AML that could become new biomarkers for risk stratification and targeted therapy in the future.…”
Section: Lncrnas In Pediatric Amlmentioning
confidence: 99%
“…Dysregulation of lncRNAs (such as lncRNA CRNDE, KCNQ1OT1, and ZFAS1) is implicated in chemoresistance in AML [10][11][12][13]. Long intergenic non coding RNAs (lincRNAs), a type of lncRNA, are emerging as key regulators in cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…While the molecular mechanisms of action for greater than 95% of lncRNAs are not clear to date, an increasing number of studies are identifying lncRNAs that have critical roles in cancer, including AML (Mishra et al, 2022 ). Over the last 3 years, other reviews have discussed the role of noncoding RNAs in hematological malignancies, however, they have focused on other noncoding RNA species such as microRNAs and circRNAs or have looked at lncRNAs in a pediatric setting (Bhattacharya & Gutti, 2022 ; Y. Liu et al, 2019 ; Neyazi et al, 2022 ). In this review, we analyze recent findings in the field of lncRNAs in AML with a focus on the specific mechanisms of lncRNAs in AML such as driving proliferation, differentiation block, therapy resistance as well as their function as tumor suppressors and utility as AML biomarkers.…”
Section: Introductionmentioning
confidence: 99%